Beyond Numbers: The Liminal Experience of Kidney Transplantation Amongst Young Adults Following Transfer of Care - Bogue Kerr, MA, MSW, Stephanie; Souliere, PhD, Marguerite; Bell, MD, FRCPC, Lorraine (The Journal of Nephrology Social Work, 2018)
Young adults who receive kidney transplants have unique needs. Adherence with medical therapy and with appointments can be a major challenge for this population, as is the transfer from pediatric to adult care. There is little qualitative research that tackles the experience of transplantation amongst young people, and still less from a social work standpoint. The present article reflects the findings of a qualitative, phenomenological study into the transition experience of young-adult kidney transplant recipients. The study found that for these young people, health professionals were involved in their relationship to their bodies. A major theme that emerged was the relational nature of the transfer of care. Finally, the article closes with a discussion of the micro- and macro-level factors that shape these relationships and the implications of these findings for nephrology social workers and other health professionals practicing in adult care settings.